Peran Kelurahan Dalam Pengawasan Pengelolaan Sampah Di Kelurahan Asam Kumbang Kecamatan Medan Selayang Kota Medan - Endang Wastiani; R. Hamdani Harahap; Isnaini Isnaini (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The purpose of this study was to determine the role of urban village in monitoring trash management at urban village of Asam Kumbang District. One of the goals is to overcome the trash problem by carrying out management actions so that the volume of trash can be controlled and to find out the inhibiting factors in implementing the urban village role. When the amount of trash increases, it will cause problems that can be harmful to humans, both health and the environment. Therefore, it is important to involve village officials as the government closest to the people. The type of research used is qualitative research with the type of research, namely the phenomenological type and the number of informants is 4 people. This research method uses empirical research methods with a statutory approach, to obtain data, researchers conduct observations and interviews with the urban village government, and the community using purposive sampling. The results of the study revealed that the role of the urban village government was in accordance with Law No. 18 of 2008 concerning Trash Management. As for the inhibiting factors, namely, community factors, facility factors and urban village government factors.